The Tax Burden CGE Analysis for Slovakia and Slovenia - Mitkova, Veronika; Jánošová Miroslava (Naše gospodarstvo/Our economy, 2019)
In the paper, the static computable general equilibrium model for Slovakia and Slovenia is used for a tax burden analysis. There was considered simultaneous 1% increase in taxes on primary factors, on firms’ and government domestic and imported purchases, on import taxes, on output (or income) tax, on private domestic and imported consumption taxes and export subsidies. The direct tax burden as well as the allocative efficiency effects of a tax, the welfare effects and welfare decomposition of such change for both countries is analysed. The most sensitive sectors on tax rate changes is heavy manufacturing and processed food and the most distorting effect has the tax increase on private consumption tax. The government’s tax increase should generate return at least 105.75% of its costs in Slovakia and 101.92% in Slovenia, otherwise the welfare will decline.